THE EFFECT OF JUNK FOOD FOR CHILDREN IN DEVELOPMENT COUNTRIES - Nadya Novenia (JUMP Health (Journal of Ultimate Public Health), 2017)
One labelled “junk” was associated with increased consumption of high-fat processed foods (burgers,coated poultry) and snack foods high in fat and /or sugar (such as crisps, and chocolate),which tend to be of poor nutritional quality.(1) behavior is leading to the weight gain, increased blood pressure, and increased cholesterol levels that are contributing to diabetes epidemics and our current obesity. childhood obesity is a major public health problem. In 2009–2010 in children and adolescents aged 2–19 y,it was estimated that 15% of them were overweight, and 17% of them were obese.(2)